Predictors of User Engagement With Facebook Posts Generated by a National Sample of Lesbian, Gay, Bisexual, Transgender, and Queer Community Centers in the United States: Content Analysis - Goedel, William C; Jin, Harry; Sutten Coats, Cassandra; Ogunbajo, Adedotun; Restar, Arjee J (JMIR Publications, 2020)
BackgroundLesbian, gay, bisexual, transgender, and queer (LGBTQ) community centers remain important venues for reaching and providing crucial health and social services to LGBTQ individuals in the United States. These organizations commonly use Facebook to reach their target audiences, but little is known about factors associated with user engagement with their social media presence. ObjectiveThis study aimed to identify factors associated with engagement with Facebook content generated by LGBTQ community centers in the United States. MethodsContent generated by LGBTQ community centers in 2017 was downloaded using Facebook's application programming interface. Posts were classified by their content and sentiment. Correlates of user engagement were identified using negative binomial regression. ResultsA total of 32,014 posts from 175 community centers were collected. Posts with photos (incidence rate ratio, [IRR] 1.07; 95% CI 1.06-1.09) and videos (IRR 1.54; 95% CI 1.52-1.56) that contained a direct invitation for engagement (IRR 1.03; 95% CI 1.02-1.04), that expressed a positive sentiment (IRR 1.11; 95% CI 1.10-1.12), and that contained content related to stigma (IRR 1.16; 95% CI 1.14-1.17), mental health (IRR 1.33; 95% CI 1.31-1.35), and politics (IRR 1.28; 95% CI 1.27-1.29) received higher levels of engagement. ConclusionsThe results of this study provide support for the use of Facebook to extend the reach of LGBTQ community centers and highlight multiple factors that can be leveraged to optimize engagement.